Stress and Coping Strategies among Parents of Infants Admitted in Neonatal Intensive Care Unit at Tertiary Level Hospital - Banjade, Bishnu Maya; Pun, Khagi Maya; Khatri, Sushila; Pokharel, Sunita (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Having a newborn infant hospitalized in the NICU is an unexpected and stressful event for a family. Coping is defined by actions of self-regulation of emotions, cognitions, behaviors, and motivational orientation under stress. Present study is aimed at identifying the level of stress and coping strategies of parents of infants admitted in NICU. Methods: A cross-sectional analytical study was conducted among 104 parent of infants admitted in NICU at Patan Hospital and Kanti Children’s Hospital, Nepal. Parental stress and coping strategy was assessed using PSS:NICU scale and modified coping checklist. Descriptive (frequency, percentage, mean) and inferential statistics (Pearson’s correlation and fisher exact test) was used to analyze the data. Results: Among 104 parents, 97.12% had moderate, 1.92% had low and 0.96% had severe stress. Regarding coping strategies mostly used coping were, social coping (mean score 3.93) and emotional coping strategy (mean score 3.77). Social coping was positively correlated with overall stress level (r = 0.41). None of the parents and infants related variables were significantly associated with stress level. Conclusion: Nearly all the parents had moderate level of stress and parental role was the major stressor. More than three fourth of the parents used social and emotional coping and followed by spiritual, diversional and least used was problem solving strategy. None of the parents and infants related variables was significantly associated with stress level. Social coping was positively correlated with overall stress level.